Dual-Language Programme (DLP) implementation in Malaysian secondary schools: from the lenses of school administrators - Ashairi Suliman,; Mohamed Yusoff Mohd Nor,; Melor Md Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The implementation of Dual-Language Programme (DLP) in the Malaysian education system has entered the fourth year since its inception. Resembling the previous educational policy, DLP emphasises the use of English as a means of instruction in the teaching and learning of Science and Mathematics. The execution of the programme requires the adherence of four main regulations, including schools’ readiness to implement DLP. This study surveyed 80 school administrators’ perception of the programme, the reasons the schools decide to take part in the programme, and the challenges encountered by the school in the programme. Questionnaire and interviews were used to collect data. Findings revealed that the school administrators have positive perceptions towards the DLP programme, where they believe that DLP should be continued, yet improvements are needed to make the programme more effective. In addition, the main reason that the schools decided to take part in the programme was because they perceived that the DLP as a means to develop and improve English language mastery among the students in particular as well as the teachers indirectly. The findings implicate that the implementation of DLP needs serious attention by the school administrators, that encompasses the resources and facilities provision, human resource development as well as DLP students’ welfare.